Efecto de un dispositivo intravaginal con progesterona sobre la actividad ovárica en yeguas cíclicas - Bianchi, C.P. (2011)
The aim of the present study was to evaluate the effect of a progesterone releasing intravaginal device plus the injection of PGF2? at removal and the application of hCG on day 5 after withdrawal on the ovarian activity in cyclic mares. Additionally, pregnancy rates were evaluated at the end of the study. Animals were divided into two groups: Treated with an intravaginal device containing 1.38 g progesterone during 8 days plus PGF2? at the removal time and an hCG injection to animals with a follicle with a diameter ? 30 mm on day 5 and controls (no treatment). Four days after removal, animals were mated. Plasma progesterone concentrations remained 2.1 ng ml-1 during the period that the devices were kept into the vagina. An ovulatory follicle between the device removal and hCG application was observed in 83.4% (25/30) of the treated animals: 68% (17/25) ovulated in response to hCG while 32% (8/25) ovulated spontaneously during the fi rst 4 days post device removal. In the control group, ovulations occurred randomly. On day 45, animals were ultrasonographed for pregnancy diagnosis. It was recorded a higher percentage of pregnant mares during the fi rst days post treatment in the T group although differences were not statistically signifi cant. In summary, the use of an intravaginal device containing progesterone in a protocol as presented in this study permit an important synchronization of the appearance of ovulatory follicles around day 5 after removal. \n